The experiential Caribbean creating knowledge and healing in the early modern Atlantic - Gómez, Pablo F. (The University of North Carolina Press, 2017)
"Pablo F. Gómez examines the strategies that Caribbean people used to create authoritative, experientially based knowledge about the human body, healing, and the natural world during the long seventeenth century. Gómez treats the early modern intellectual culture of these mostly black and free Caribbean communities on its own merits and not only as justified by how it relates to well known frameworks for the study of science and medicine"...
Keywords: Geschichte 1600-1700; Geschichte; Traditional medicine -- Caribbean Area -- History -- 17th century; Healing -- Caribbean Area -- History -- 17th century; Experiential learning -- Caribbean Area -- History -- 17th century; Free blacks -- Caribbean Area -- History -- 17th century; Volksmedizin; Schwarze; Karibik